Hierarchical porous photosensitizers with efficient photooxidation - Yajun Fang; Yuntian Yang; Rui Xu; Mingyun Liang; Qi Mou; Shuixia Chen; Jehan Kim; Long Yi Jin; Myongsoo Lee; Zhegang Huang (Nature Communications, 2023)
Abstract Photosensitizers (PSs) with nano- or micro-sized pore provide a great promise in the conversion of light energy into chemical fuel due to the excellent promotion for transporting singlet oxygen (1O2) into active sites. Despite such hollow PSs can be achieved by introducing molecular-level PSs into porous skeleton, however, the catalytic efficiency is far away from imagination because of the problems with pore deformation and blocking. Here, very ordered porous PSs with excellent 1O2 generation are presented from cross-linking of hierarchical porous laminates originated by co-assembly of hydrogen donative PSs and functionalized acceptor. The catalytic performance strongly depends on the preformed porous architectures, which is regulated by special recognition of hydrogen binding. As the increasing of hydrogen acceptor quantities, 2D-organized PSs laminates gradually transform into uniformly perforated porous layers with highly dispersed molecular PSs. The premature termination by porous assembly endows superior activity as well as specific selectivity for the photo-oxidative degradation, which contributes to efficient purification in aryl-bromination without any postprocessing.